Slogan Of “Uhamka Lebih Utama” Effects On Brand Awareness For Senior High School Students - Moh Supendi; Mutiara Hidayati (Agregat: Jurnal Ekonomi dan Bisnis, 2020)
This study aims to reveal the effect of the slogan on brand awareness towards University of Muhammadiyah Prof. DR. HAMKAfor high school students in DKI Jakarta. The subjects for this study were all students in high schools located in Jakarta. Cluster Sampling is used to take 100 students as samples, taken from 5 schools located in 5 different regions in Jakarta, namely East Jakarta, West Jakarta, South Jakarta, North Jakarta, and Central Jakarta. In addition, this study uses descriptive quantitative associative methods. The results of this study imply that University of Muhammadiyah Prof. DR. HAMKA has a positive and significant influence on brand awareness for high school students in DKI Jakarta.